Elevated Serum Beta‐Trace Protein Levels are Associated With the Presence of Atrial Fibrillation in Hypertension Patients. Issue 5 (5th October 2015) - Yalcin, Muhammed U.; Gurses, Kadri M.; Kocyigit, Duygu; Kesikli, Sacit A.; Tokgozoglu, Lale; Guc, Dicle; Aytemir, Kudret; Ozer, Necla
Abstract : Beta‐trace protein (BTP) has emerged as a novel biomarker of cardiovascular risk. In this study, the authors aimed to assess the relationship between BTP levels and presence of atrial fibrillation in patients who had controlled hypertension (HTN) and normal renal function. A total of 80 controlled HTN patients with paroxysmal atrial fibrillation (PAF) and 80 age‐ and sex‐matched controls with controlled HTN were enrolled. Serum BTP levels were measured by enzyme‐linked immunosorbent assay. BTP levels were found to be significantly higher in patients with PAF ( P <.001). Other parameters including mean systolic and diastolic blood pressure values, serum creatinine levels, and glomerular filtration rate were similar between the two groups. Along with left atrial diameter (odds ratio, 1.504; P <.001), BTP levels (odds ratio, 1.015; P <.001) were independently associated with the presence of PAF. BTP levels were increased in controlled HTN patients with PAF compared with controls, and this association was observed within normal renal functions as reflected by normal glomerular filtration rate.